Impact of Customer Service and Value Creation on Customer Satisfaction in Modern Indian Retailing: A Clue To The Global Retailers - Rajib Roy (Abhigyan, 2012)
Retailing in India and many other emerging countries is traditionally dominated by the small unorganized retailers and has been experiencing the surge of modern format organised retailing since last few years. In this context this research article is an attempt to see the impact of customer service and value creation on customer satisfaction through such retailing format which is a new experience for Indian consumers and hence providing a strategic hint to the global retailers. The study reveals the extent to which customer service and value creation affect customer satisfaction and how to address the underlying dimensions of both these in order to improve customer satisfaction specially with respect to marketing mix elements. A measurement scale has been defined first to measure the multidimensional constructs of customer service and value creation and that of customer satisfaction using primary data collected through structured questionnaires. Later Multiple Regression Model is applied to explain the impact of customer service and value creation on customer satisfaction. The study provides significant direction for the existing and potential players to improve on service delivery and value creation using marketing mix elements more effectively, that seem to take care of retailer’s creativity and innovation at the moment, especially in the absence of private label branding. This paper provides relevant strategic guideline to the International retailers regarding the entry formats in the Indian and other emerging markets of similar nature which are new to modern retailing.